A study on Christian librarians in the Philippines and the integration of their faith in the profession - Enriquez, Kevin Vincent M. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Christian librarians are distinguishing themselves in foreign countries. They argue that they practice librarianship in a unique way. They have established large organizations such as the Association of Christian Librarianship (ACL) and the Fellowship of Christian Librarians and Information Scientists (FOCLIS) and have published numerous articles for the development of Christian librarianship. While a formal definition of Christian librarianship has yet to be formulated, close inspection of literature shows that the core characteristics of Christian librarianship is having faith in Jesus Christ and integrating that faith in librarianship. In the Philippines, information resources and even common knowledge of Christian librarianship is very scarce, leading to the question of whether it exists in the Philippines. It is in this light that this study aimed to investigate the existence of Christian librarianship in the Philippines and the extent of its practice.